Lieux et réseaux d’enfermement des migrants à la frontière orientale de la Grèce - Laurence Pillant (EchoGéo)
Migration control at Greece's eastern border is mainly based on the detention of migrants who have crossed the border without authorisation. In the 2000s, unregulated detention places with heterogeneous functions emerged. This article explores how the authorities can control migrants in these places. It consists in particular of a spatio-temporal uncertainty that reinforces the repressive and dissuasive character of liberty deprivation. These uncertainties are not limited to the scale of the place, but are combined with frequent transfers that can occur at any time. By following the forced migrants’ mobilities, this article examines the detention places functions, their multiplication and their network connections.